[11C]-Methionine Positron Emission Tomography in the Postoperative Imaging and Followup of Patients with Primary and Recurrent Gliomas. (4th February 2014) - Santoni, Matteo; Nanni, Cristina; Bittoni, Alessandro; Polonara, Gabriele; Paccapelo, Alessandro; Trignani, Roberto; De Lisa, Mariagrazia; Rychlicki, Franco; Burattini, Luciano; Berardi, Rossana; Fanti, Stefano; Cascinu, Stefano
Abstract : We investigated the sensitivity and specificity of [ 11 C]-methionine positron emission tomography ([ 11 C]-MET PET) in the management of glioma patients. We retrospectively analysed data from 53 patients with primary gliomas (16 low grade astrocytomas, 15 anaplastic astrocytomas and 22 glioblastomas) and Karnofsky Performance Status (KPS) > 70. Patients underwent [ 11 C]-MET PET scans (N = 249 ) and parallel contrast-enhanced MRI (N = 193 ) and/or CT (N = 113 ) controls. In low grade glioma patients, MRI or CT findings associated with [ 11 C]-MET PET additional data allowed discrimination residual disease from postsurgical changes in 96.22% of these cases. [ 11 C]-MET PET early allowed detection of malignant progression from low grade to anaplastic astrocytoma with high sensitivity (91.56%) and specificity (95.18%). In anaplastic astrocytomas, we registered high sensitivity (93.97%) and specificity (95.18%) in the postoperative imaging and during the followup of these patients. In GBM patients, CT and/or MRI scans with additional [ 11 C]-MET PET data registered a sensitivity of 96.92% in the postsurgical evaluation and in the tumour assessment during temozolomide therapy. A significant correlation was found between [ 11 C]-MET mean uptake index and histologic grading (P < 0.001 ). These findings support the notion that complementary information derived from [ 11 C]-MET PET may be helpful in postoperative and successive tumor assessment of glioma patients.